Integrative Diniyah Curriculum in Formal Schools at Tebuireng Pesantren Jombang - Sholihuddin, Ahmad; Nidak, Khoiru (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
This article explores the steps of diniyah integration in formal institutions, improving the quality of diniyah learning organization, and developing diniyah integration in formal institutions in Tebuireng. With a qualitative approach and case study type, the primary data is in the form of learning activities at SMP A. Wahid Hasyim and MTs Salafiyah Syafi'iyah Tebuireng Jombang, curriculum structure documents and learning tools, with resource persons the manager and teachers, and learning activities. Data collection uses documentation, interviews, and observation, with data analysis techniques according to Miles Huberman's theory. The results of the study show that integration with the integrative-interconnective model is in the form of incorporating the curriculum of madrasah diniyah pondok pesantren with the levels of I'dâd, Ûlâ, Wusthâ, and 'Ulyâ into schools through adjustments to grade levels 7, 8, and 9. Starting from the calculation of hours and subjects of diniyah, then identifying students based on the level of madrasah diniyah pondok pesantren, which results in the integration of Ûlâ classes in major to junior and senior high schools, and Wusthâ in minor. For MTs, the Wusthâ class curriculum is integrated in major and ‘Ulyâ in minor. The MA level integrates the ‘Ulyâ class fifty-fifty with the Wusthâ class. Improving the quality of teachers through debriefing, ongoing academic activities, and coaching. Teacher supervision becomes a direct and factual entrance to the findings and problems faced by diniyah teachers, also through the Subject Teacher Conference (MGMP) forum. Development of diniyah integration in the form of HR supervision through MGMP and the content of diniyah lessons as well as the restructuring of lesson hours.